Analysis of the mezcal value chain in San Felipe, Guanajuato - Cervantes Luna, Juan Oswaldo; Hernández Ortiz, Juan; Valdivia Alcalá, Ramón; Melo Guerrero, Enrique; Sandoval Romero, Fermín; González Juárez, Araceli (Revista Mexicana de Ciencias Agrícolas, 2022)
The concept of value chain has been developed due to the need for rural companies to meet the requirements of the demand for high-quality specialized products. The value chain methodology allows us to make a diagnosis of the current situation. Subsequently, we can make an analysis of the actors involved in it and develop strategies that help improve the activity. This research work analyzes the mezcal value chain of San Felipe, from the point of view of the producers themselves to identify the links in the value chain. Information was collected through surveys and structured interviews. The information indicates that the mezcal value chain in the municipality is at a low level of competitiveness. In addition, it is disjointed in both horizontal and vertical relationships. A greater commitment on the part of the actors is recommended to be able to strengthen the relationships between the links of the chain, as well as to promote training and technical assistance in the different areas of production and to call on research and teaching institutions for the development of competitiveness strategies.
Keywords: Mezcal; Diagnosis; horizontal relationship; vertical relationship; cooperation